THU0588 Are rheumatoid arthritis patients willing to use an e-health interactive self-assessment website? analyses of 159 patients from a randomised controlled trial over 12 months. (15th June 2017) - Gossec, L; Cantagrel, A; Soubrier, M; Joubert, JM; Czarlewski, W; Combe, B; Berthelot, JM; Wendling, D; Dernis, E; Grange, L; Beauvais, C; Perdriger, A; et al.
Abstract : Background: Interactive, online electronic (e)-health services with patient-reported outcome measure (PROM)-based instruments may be helpful for patients (pts). Sanoïa is a secure, independent e- and mobile (m)-health platform developed to allow pt self-assessment, storage of questions to ask physicians, and self-monitoring of disease status. The platform offers a dedicated set of scores, PROMs and information about different diseases, including rheumatoid arthritis (RA). Objectives: To characterise pts with RA who chose to access e-health services regularly over a 12-month (mo) period. Methods: Post-hoc analysis of CarNET (NCT02200068 ): a French, multicentre, 12-mo randomised controlled trial. Pts with RA were randomised to: access to Sanoïa (30-min training via the telephone with no further incentive to access the platform) or usual care (normal internet use without access to Sanoïa). The Sanoïa group pts used a home-based e-Case Report Form to record frequency of Sanoïa access, satisfaction with the platform (0–10 scale; 0=completely satisfied, 10=not satisfied), and barriers to use (from a pre-specified list). Baseline pt characteristics associated with more frequent use (above the median) were analysed by univariate and multivariate logistic regression. Results: 159 RA pts were randomised to the Sanoïa arm: mean±SD age was 56.1±13.1 years, disease duration was 15.0±11.5 years and 132 (83.0%) of pts were female. Mean DAS28 was 2.7±1.2 with 57.2% of pts in remission; 115 (72.3%) were taking a biologic; 23.3% had attended therapeutic education sessions; 15.7% were members of pt associations; and 53.5% had participated in university-level studies. Overall, 41 pts (25.7%) never accessed Sanoïa and 81 (50.9%) accessed the platform at least twice; median=2, mean±SD=4.4±11.3 connections/pt over the 12 mos. 54 pts (34.0%) used Sanoïa for ≥2 mos with a noticeable investigator effect (0.3±0.2, 0–1 scale). Mean satisfaction with the platform was very high (1.5±1.5), with 90% scoring satisfaction ≤3. One barrier was expressed in 11.8% of cases: "the platform is not useful for me since I am in remission". In multivariate analysis, the only variable associated with greater usage of Sanoïa was being a member of a pt association: odds ratio [95% CI]=1.44 [1.17–1.77]. Conclusions: A quarter of pts who participated in this trial to assess e-health did not access the platform whereas half accessed the platform at least twice. Pts expressed high satisfaction and the only barrier was lower usefulness when in remission. e-Health is a promising tool for self-management in RA. The impact of offering additional services should also be explored in a further study. Acknowledgements: This study was funded by UCB Pharma. We thank the patients and their caregivers in addition to the investigators and their teams who contributed to this study. Editorial services were provided by Costello Medical Consulting. Disclosure of Interest: L. Gossec Grant/research support from: UCB Pharma, Lilly, Consultant for: AbbVie, BMS, Celgene, Janssen, Novartis, MSD, UCB, A. Cantagrel: None declared, M. Soubrier: None declared, J. M. Joubert Employee of: UCB Pharma, W. Czarlewski Employee of: UCB Pharma, B. Combe Grant/research support from: Merck Pfizer Inc, Roche-Chugai, Consultant for: Merck, Pfizer, Roche-Chugai, UCB Pharma, Bristol-Myers Squibb, Celgene, Eli Lilly, Speakers bureau: Merck, Pfizer, Roche-Chugai, UCB Pharma, Bristol-Myers Squibb, Celgene, Eli Lilly, Novartis, J. M. Berthelot: None declared, D. Wendling: None declared, E. Dernis: None declared, L. Grange: None declared, C. Beauvais Speakers bureau: UCB Pharma, A. Perdriger: None declared, H. Nataf: None declared, M. Dougados Grant/research support from: UCB Pharma, AbbVie, Pfizer, Lilly, Merck, Novartis, H. Servy Shareholder of: Sanoïa platform operating company: e-health services, Employee of: Sanoïa